Uchwały antysmogowe a prawa konsumenta - Krawczyk, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Anti-smog resolutions, established by the Environment Protection Law, have become one of the most important tools of air quality protection in Poland. The voivodeship councils have gained the competence to regulate the exploitation of installations in which the fuels are combusted. This very problem can be analyzed as a consumer protection law issue as the addressees of resolutions are undoubtedly consumers buying the fuels. The elaboration of the issue provides the examination of some of the resolutions already enacted and their influence on consumers practices.
Keywords: anti-smog resolutions; consumer protection law; self-government